REGIONAL FEATURES OF AGRICULTURAL AREAS AND THEIR IMPACT ON SOCIAL AND GEOGRAPHIC PROCESS AFTER THE REFORM OF 1861 (FOR EXAMPLE, POLTAVA REGION) - Лавриненко, Сергій (Human Geography Journal, 2015)
The paper deals with the influence of socio-economic factors on the evolution of the agricultural sector of Poltava in the aftermath of the peasant reform of 1861 and their impact on the socio-geographical processes. The author analyzes the complex transformation of the conditions and trends of agricultural production in Ukraine in the period of industrial society. Revealing the nature of post-capitalist evolution ofagriculture by regional features discovers development of agriculture by analyzing various natural and social factors influence.